2022
DOI: 10.3389/fpsyg.2022.1038169
|View full text |Cite
|
Sign up to set email alerts
|

Money lies and extramarital ties: Predicting separate and joint occurrences of financial deception and extramarital infidelity

Abstract: IntroductionAlthough spouses frequently financially deceive each other (MFD; i.e., marital financial deception), few studies have examined this relationship behavior. The purpose of our study is to examine predictors of separate and joint occurrences of MFD and extramarital affairs (EMI). We chose the predictors we tested using social exchange theory (SET).MethodsWe used a national sample of married individuals and multinomial logistic regression analyses to examine how different predictors were associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Dew et al, explored two kinds of marital deceptions: financial marital deception (FMD) and extramarital infidelity (EMI) [87]. EMI was well researched, while MFD was much less so.…”
Section: Marital Deceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dew et al, explored two kinds of marital deceptions: financial marital deception (FMD) and extramarital infidelity (EMI) [87]. EMI was well researched, while MFD was much less so.…”
Section: Marital Deceptionmentioning
confidence: 99%
“…This may lead to a situation in which a spouse may be dissatisfied with the marriage, but viewing it as a long-term commitment will motivate them to invest in it and be less interested in alternative relationships, despite their present unhappiness [92]. Recent research about MFD and EMI found that personal dedication commitment (in the form of marital stability and trust of one's partner) is negatively associated with MFD [87]. Additionally, personal dedication commitment is associated with a lower level of sexually unfaithful behaviors [93].…”
Section: Moral Commitmentmentioning
confidence: 99%